2018
DOI: 10.5194/we-18-67-2018
|View full text |Cite
|
Sign up to set email alerts
|

Are post-dispersed seeds of <i>Eucalyptus globulus</i> predated in the introduced range? Evidence from an experiment in Portugal

Abstract: Abstract. Plantations of Eucalyptus globulus Labill. have been expanding rapidly worldwide. The species is considered invasive in several regions. While in the native range, post-dispersal seed predation is known to severely limit eucalypt recruitment, there is no experimental evidence of seed predation in the introduced range. We hypothesised that E. globulus seeds largely escape predation in Portugal, which may explain its prolific recruitment in some locations. We tested this hypothesis in central Portugal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 82 publications
(141 reference statements)
0
4
0
Order By: Relevance
“…Seeds have higher germination success if adequate moisture conditions are met shortly after dehiscence. The shorter the time-lag between dehiscence and germination cues, the higher will be the probability that seeds will escape predation and natural decay [58,59]. The fire occurred unusually late in early autumn (15 October), two days before significant rainfall (13 mm).…”
Section: Wildling Establishmentmentioning
confidence: 99%
“…Seeds have higher germination success if adequate moisture conditions are met shortly after dehiscence. The shorter the time-lag between dehiscence and germination cues, the higher will be the probability that seeds will escape predation and natural decay [58,59]. The fire occurred unusually late in early autumn (15 October), two days before significant rainfall (13 mm).…”
Section: Wildling Establishmentmentioning
confidence: 99%
“…The consumption of alien seeds by seed predators is observed elsewhere (Blaney & Kotanen 2001;Nuñez et al 2008;Pearson et al 2014;Preukschas et al 2014;Deus et al 2018;Montesinos et al 2018). In agreement with other studies, the removal rates of our alien seeds were lower (Shahid et al 2009;Connolly et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, post-dispersal seed predators are often generalists and readily consume new food items of great energetic value (Kelrick et al 1986), and their activity can provide biotic resistance against alien plant invasion in some contexts (Nuñez et al 2008;Pearson et al 2011Pearson et al , 2014. However, the response of granivores to invasive species is highly variable, and studies comparing seed removal of native and invasive species have found controversial findings (Blaney & Kotanen 2001;Shahid et al 2009;Connolly et al 2014;Preukschas et al 2014;Deus et al 2018;Montesinos et al 2018). The identity of granivores and their preferences for native seeds over exotic seeds can be important for the outcome of invasion (reviewed by Parker et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…At a local scale, studies in Portugal have shown saplings were more abundant on moist aspects [14], and spread more along natural drainage lines and in the direction of the prevailing wind [19]. At this local scale, the likelihood of sapling establishment has also been shown to depend upon the reproductive output of the E. globulus source population [11,15,19], adjacent plant community type [18,49], fire [11,15,17,80,81] and, potentially, levels of seed predation [80,82].…”
Section: Naturalization In Californiamentioning
confidence: 99%